Prediction Of Job Selection Among Faculty Of Computing Students - Ong, Hui Gie (2023)
There are many jobs in the computer science and information technology field. As technology keeps improving, there are many new careers generated and obviously, job selection in this field will be more and more. This project is aims to help the students from Faculty of Computing in University Malaysia Pahang (UMP) in order to obtain the information about the career can be applied after their graduation. This is vital as every job has different knowledge that needs to be mastered. If the students can obtain the skills and knowledge in the university, it will help the students to get the jobs easier in their future day after graduation. In the university perception, by analysing the job career selected by the graduates, they can make the decision on whether to open or close a class to follow the market demand, or to update the current syllabus. By doing so, the university will have the higher ranking with high employment rate. All attributes have been identified. The techniques include in the project is machine learning that used to analyses the data of the graduated. The techniques selected were from the previous study, which is SVM, MLP, and CART. The best technique is SVM with the highest accuracy among these three techniques. Prediction on the career for future Faculty of Computing students is also a part of the scope for this project. This project enables students to have a clear idea for the future job they can apply for, so they can find more information and more focus. The output is shown in a dashboard, using Google Data Studio.